Pengaruh Kedisiplinan Dan Kepedulian Kepada Teman Terhadap Prestasi Belajar Siswa Kelas IV SD Negeri Ngadirejo 2 Kartasura Tahun Pelajaran 2014/2015 - Ningrum, Wati (2016)
The purpose of this study are to determine 1) the influence of discipline to student learning achievement, 2) the influence of care to friends to student learning achievement, 3) the influence of discipline and care to friends to learning achievement of grade IV students in state elementary school of Ngadirejo 2 Kartasura Academic year of 2014/2015. Type of this study is quantitative research. Total population and sample in this study are 19 students of fourth grade of state elementary school of Ngadirejo 2 Kartasura academic year of 2014/2015 which was obtained by saturation sampling technique. The technique of collecting data using questionnaires and documentation. Data analysis technique used is multiple regression analysis, t-test, F and Relative Contribution and Effective Contribution. The results showed that the test results of multiple linear regression obtained regression coefficient value of discipline is 0.209, regression coefficient of care to a friend is 0.138; F test result obtained Fcount > Ftable (69,290 > 3,59); Regression test X1 obtained tcount > ttable (3,189>2,119), regression test X2 obtained tcount > ttable (2,228> 2,119). Based on the results of this study concluded: 1) Discipline effecting on student achievement, 2) Care to friends effecting on student achievement, 3) Discipline and care to friends effecting on student achievement of fourth grade of state elementary school of Ngadirejo 2 Kartasura academic year of 2014/2015.